Dyadic effects of illness perception and maladaptive cognitive-emotional regulation strategies on the fear of cancer recurrence in breast cancer patients and spouses: an actor-partner interdependence mediation model - Hui Ren; Tianye Yang; Songli Mei; Zhu Zhu; Jianjun Shi; Lingling Tong; Jia Yang; Yabin Sun (BMC Psychiatry)
Abstract Purpose Breast cancer, as a stressful event, profoundly impacts the entire family, especially patients and their spouses. This study used a dyadic analysis approach to explore the dyadic effects of illness perception on the fear of cancer recurrence (FCR) and whether maladaptive cognitive-emotional regulation strategies acted as a mediator in breast cancer patient-spouse dyads. Methods This was a cross-sectional study, and 202 dyads of breast cancer patients and their spouses were enrolled. Illness perception, maladaptive cognitive-emotional regulation strategies, and FCR were assessed by the Brief Illness Perception Questionnaire (BIPQ), the Cognitive Emotion Regulation Questionnaire (CERQ), and the Fear of Cancer Recurrence Inventory Short Form (FCRI-SF), respectively. Data were analyzed using the actor-partner interdependence mediation model. Results This study found that, for patients and spouses, maladaptive cognitive-emotional regulation strategies mediated the actor effects of illness perception on FCR. That is, illness perception was positively related to their maladaptive cognitive-emotional regulation strategies, which increased the risk of FCR. Another important finding was that patients’ illness perception had significant direct and indirect effects on spouses’ FCR through spouses’ maladaptive cognitive-emotional regulation strategies. Conclusions Negative illness perception perceived by patients and spouses can increase their FCR by adapting their maladaptive cognitive-emotional regulation strategies. Furthermore, illness perception perceived by patients can also increase spouses’ FCR through spouses’ maladaptive cognitive-emotional regulation strategies. Medical staff should identify vulnerable patients and spouses with higher illness perception and maladaptive cognitive-emotional regulation strategies and make focused interventions to decrease the risk of FCR of both breast cancer patients and their spouses.